Efficacy and Safety of Hou Gu Mi Xi on Spleen Qi Deficiency in Patients with Nonorganic Gastrointestinal Disorders: Protocol for a Multicenter, Randomized, Placebo-Controlled Trial. (2nd December 2018) - Chen, Xiaofan; Nie, Heyun; Liu, Wenjun; Zhou, Xu; Nie, Jianhua; Xie, Bin; Chen, Dongping; Jiang, Yiping; Zhang, Kunhe; Fu, Ying; Yang, Deping; Xiong, Yan; et al.
Abstract : Background. There is a worldwide epidemic of nonorganic gastrointestinal disorders (NOGDs), which are a class of disorders that cause various discomforts and ultimately progress into organic gastrointestinal diseases. Because of the unsatisfactory efficacy of Western medical treatments, traditional Chinese medicine (TCM) is becoming a promising complementary and alternative treatment to manage NOGDs. Objectives . To investigate the efficacy and safety of Hou Gu Mi Xi (HGMX), a newly developed dietary TCM formula, on the syndrome of spleen qi deficiency (SQD) in patients with NOGDs. Methods/Design. This study is a multicenter, randomized, double-blinded, parallel, and placebo-controlled trial that will last for 2 years. All qualified subjects with NOGDs and SQD will be included. The study population will be divided into the HGMX and placebo groups. To assess the efficacy of HGMX, we will mainly focus on changes in SQD symptoms scored by a Spleen Qi Deficiency Symptoms Grading and Quantifying Scale and evaluate changes in gastrin-17, the negative Helicobacter pylori conversion rate, body weight, body mass index, and gastroscopy findings. The safety of HGMX will be assessed by recording adverse events (AEs), severe AEs, treatment-related AEs and withdrawal due to AEs. Discussion. This trial is part of our study series that intends to validate the potential of HGMX in the management of chronic gastrointestinal diseases. This series of RCTs is the first committed to the evaluation of a dietary TCM formula and will hopefully establish an evidence-based clinical research model for dietary TCM formulas. Ethics . The protocol was approved by Ethics Committee of five research hospitals and was registered in Clinicaltrials.gov (NCT03019042 ).